Karakteristik Enkapsulat Ekstrak Kulit Buah Kakao (Theobroma cacao L.) pada Perlakuan Variasi Jenis dan Konsentrasi Bahan Penyalut - Zen, Misbach Baihaqi; Ganda Putra, G.P.; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 3 (2021): SeptemberDO - 10.24843/JRMA.2021.v09.i03.p09, 2021)
This study aims to determine the effect of variations in type and concentration of coating material on the characteristics of the cocoa pod extract encapsulate and to determine the best produce cocoa pod extract encapsulate. The experimental design used in this research was a factorial randomized block design, which are grouped into 2 groups based on the implementation time and consisted of two factors . The first factor is the type of coating material (S) which consists of maltodextrin and gum arabic. The second factor is the concentration of coating material (M) which consists of: 5%, 10%, 15%, 20%, 25%. The results showed that the type and concentration of coating material had a significant effect on the yield, water content, solubility, antioxidant capacity, total phenolic and encapsulation efficiency of cocoa pod extract encapsulate. The interaction between treatments had a significant effect on the yield, solubility, antioxidant capacity, total phenolic and encapsulation efficiency, but had no effect on the water content of the encapsulated cocoa pod extract. The best treatment was obtained using gum arabic of 5% concentration coating material, with characteristics of 84.81±0.15% yield, 7.10% water content, 84.26±0.06% solubility, 80.12 ±0.24 mg GAEAC/g antioxidant capacity,  113.77±0.24 mg GAE/g total phenolic, and 78.16±0.60% encapsulation efficiency. Keywords : Antioxidants, cocoa pod, encapsulation, concentrations, gum arabic, maltodextrin.